Business Strategies for Sustainable Healthcare Delivery Through Public-Private Partnerships - Senthilkumar , Dr.C.B.; Chandrasekeran , Dr. Indhumathi; Dharmaraj , Dr.A.; Maur , Dr. Shyam; Anand , Dr. Utkarsh (International Journal of Accounting and Economics Studies, 2025)
Public-Private Partnerships (PPPs) have emerged as a strategic approach to enhancing healthcare delivery by leveraging the strengths of both sectors. This study explores business strategies that contribute to the sustainability and efficiency of healthcare PPPs. It examines financial models, governance frameworks, risk management approaches, and technology integration to assess their impact on healthcare accessibility, affordability, and quality. Using a mixed-method research approach, the study analyses successful PPP case studies, industry best practices, and stakeholder perspectives. Conclusions highlight strategic cooperation, regulatory policies, and an important role of innovative financing in ensuring the long-term viability of healthcare PPP. The study provides policy recommendations for the adaptation of the PPP structure to improve healthcare stability and efficiency.